Strategi Pengembangan Usaha CV Tungayua Menggunakan Business Model Canvas - Julia Beatrix Nanga; Ismail Yusuf; Nizza Nadya Rachmani (Jurnal Informatika Ekonomi Bisnis, 2023)
Competition between printing companies is getting tougher, so CV Tungayua must be able to create opportunities to survive in the midst of intense competition. One way that CV Tungayua can do to survive is to create a business strategy that is developed after knowing the current business model and evaluating the business model being carried out. This study aims to identify the CV Tungayua business model using the Business Model Canvas (BMC), evaluate the implemented business model, and devise a strategy for improvement for the development of the evaluation of the CV Tungayua business model that has been carried out. The method used is qualitative with analytical tools used by BMC and Tolo Branca's assistance as an evaluation of strengths, weaknesses, opportunities and threats. The results of the study show the identification of nine business model elements which indicate that the main strength comes from the value proposition block with the programs offered being able to meet and adapt customer needs. Meanwhile, the main weakness comes from revenue streams that have small margins. The main opportunities come from channels and the main threats come from main activities. The strategy that can be carried out is to optimize the key activity elements and revenue streams combined with the opportunities and strengths of the channel and value proposition to produce a strategy that provides development for CV Tungayua in South Jakarta City.